2012
DOI: 10.1007/s00239-012-9514-3
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of the Shell Matrix Protein Aspein in Pterioid Bivalves

Abstract: Aspein is one of the unusually acidic shell matrix proteins originally identified from the pearl oyster Pinctada fucata. Aspein is thought to play important roles in the shell formation, especially in calcite precipitation in the prismatic layer. In this study, we identified Aspein homologs from three closely related pterioid species: Pinctada maxima, Isognomon perna, and Pteria penguin. Our immunoassays showed that they are present in the calcitic prismatic layer but not in the aragonitic nacreous layer of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 22 publications
0
29
0
Order By: Relevance
“…It is known that the GXN repeat may display different functions related to calcification: (1) it may interact with calcium ions in solution, by behaving as a low affinity, high capacity calcium-binding domain, and could therefore be involved in CaCO 3 nucleation [98,99]. This suggests that nacreins work as both as enzymes, converting CO 2 into bicarbonate, and also as CaCO 3 nucleating polymers.…”
Section: Low Complexity Domains (Lcds) In α-Cas Related To Caco 3 Biomentioning
confidence: 99%
“…It is known that the GXN repeat may display different functions related to calcification: (1) it may interact with calcium ions in solution, by behaving as a low affinity, high capacity calcium-binding domain, and could therefore be involved in CaCO 3 nucleation [98,99]. This suggests that nacreins work as both as enzymes, converting CO 2 into bicarbonate, and also as CaCO 3 nucleating polymers.…”
Section: Low Complexity Domains (Lcds) In α-Cas Related To Caco 3 Biomentioning
confidence: 99%
“…Parallel studies in the field of life science using genetic research have recently made rapid progress. In pearl research, genome analysis is also making rapid progress (Shen and Morse, 1997;Kono et al, 2000;Zhang and Zhang, 2003;Wang et al, 2008Wang et al, , 2009, and there have been many significant studies in the field of biomineralization, such as the elucidation of the nacre-forming mechanism (Suzuki et al, 2009;Jackson et al, 2010;Joubert et al, 2010;Kinoshita et al, 2011;Fang et al, 2011;Gardner et al, 2011;Montagnani et al, 2011;Isowa et al, 2012;Marie et al, 2012;Wang et al, 2012). An important milepost was reached in 2012 when, in a world first, a group including the Okinawa Institute of Science and Technology Graduate University and others performed draft genome sequencing of the Japanese Akoya oyster (Takeuchi et al, 2012).…”
mentioning
confidence: 99%
“…Although hundreds of SMPs are expected to contribute to shell formation, little is known about their evolutionary histories, with only few studies conducted on metazoan biomineralisation-related genes (Sarashina et al 2006, Jackson et al 2010, Marie et al 2011a, Miyamoto 2012, Werner et al 2013) and molluscan-specific gene families (Isowa et al 2012, McDougall et al 2013a, Song et al 2014 Despite these difficulties, studies have revealed that SMP gene families, such as the shematrins and KRMPs, have undergone rapid and independent lineage-specific gene expansions and extensive sequence divergence and speciation events (McDougall et al 2013a), supporting the proposition that SMPs are fast evolving (Jackson et al 2006). …”
Section: Shell Matrix Protein Evolution Reveals Rapid and Independentmentioning
confidence: 99%
“…It has been observed that some well conserved amino acid residues present in proteins with repetitive low complexity domains (RLCD-containing proteins) are encoded by heterogeneous DNA repeats (e.g. N14, N16, KRMP, shematrin and Aspein) (Samata et al 1999, Kono et al 2000, Yano et al 2006, Zhang et al 2006b, Isowa et al 2012. Because of this repetitiveness, these proteins are susceptible to different evolutionary mechanisms, including point mutations that may cause variation in amino acid composition, as well as replication slippage and unequal crossover that could explain the expansion and contraction of repeat amino acid sequences.…”
Section: The Molecular Basis and Modes Of Shell Matrix Protein Evolutionmentioning
confidence: 99%
See 1 more Smart Citation